SOSIALISASI ADMINISTRASI DESA DI DESA BANGKA KANTAR KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR - Amu Oyan, Maria Fransiska; Santoso Lowa, Yosep Copertino; Ayu Lawalu, Stephanie Perdana; Yanto, Marianus Diaz (Merwinspy Publisher, 2025)
Administration is one of the sources for obtaining data and information. Administrative management often encounters obstacles, especially in terms of archiving, which frequently occurs in the Village. The purpose of implementing this socialization activity is to increase the knowledge and understanding of the Village government and the Community in the arrangement of Village administration in Bangka Kantar Village, Borong District, East Manggarai Regency. The socialization material includes General Understanding of Administration, Village Understanding Administration, Types of Village Administration, and the benefits of implementing effective and efficient administration. This implementation method is carried out through observation, coordination and implementation of activities. Participants involved in this activity are village officials and the community in Bangka Kantar Village, Borong District, East Manggarai. The results of the activity are expected to provide education and practical practice to the village government and community, so that better and neater village administration governance is realized.